Oya : in praise of an African goddess - Gleason, Judith Illsley (New York : Harper Collins Publishers, 1992)
Originally published: Boston: Shambhala, 1987. With new introd.
Includes bibliographical references.
Keywords: Oya (Yoruba deity); Yoruba (African people) -- Religion